Graphene oxide-based substrate: physical and surface characterization, cytocompatibility and differentiation potential of dental pulp stem cells. Issue 8 (August 2016) - Rosa, Vinicius; Xie, Han; Dubey, Nileshkumar; Madanagopal, Thulasi T.; Rajan, Sneha S.; Morin, Julien Luc Paul; Islam, Intekhab; Castro Neto, Antônio Hélio
Abstract: Objective: The aim of this study was to evaluate the cytotoxicity and differentiation potential of a graphene oxide (GO)-based substrate using dental pulp stem cell (DPSC). Methods: GO was obtained via chemical exfoliation of graphite using the modified Hummer's method and dispersed in water-methanol solution. 250 μL of 1.5 mg/mL solution were added to a cover slip and allowed to dry (25 °C, 24 h). GO-based substrate was characterized by Raman spectroscopy, AFM and contact angle. DPSC were seeded on GO and glass (control). Cell attachment and proliferation were evaluated by polymeric F-actin staining, SEM and MTS assay for five days. mRNA expression of MSX-1, PAX-9, RUNX2, COL I, DMP-1 and DSPP were evaluated by qPCR (7 and 14 days). Statistical analyses were performed by either Mann–Whitney, one or two-way Anova followed by and Tukey's post hoc analysis ( α  = 0.05). Results: Peaks at 1587 cm −1 and 1340 cm −1 (G and D band) and ID/IG of 0.83 were observed for GO with Raman. AFM showed that GO was randomly deposited and created a rougher surface comparing to the control. Cells successfully adhered on both substrates. There was no difference in cell proliferation after 5 days. Cells on GO presented higher expression for all genes tested except MSX-1 and RUNX2 for 7 days. Significance: GO-based substrate allowed DPSC attachment, proliferation and increased the expression of several genes that are upregulated in mineral-producing cells. These findings open opportunities to the use of GO alone or in combination with dental materials to improve their bioactivity and beyond.